2008
DOI: 10.1590/s0102-36162008000300003
|View full text |Cite
|
Sign up to set email alerts
|

Modelo experimental para o estudo da hérnia do disco intervertebral

Abstract: RESUMOObjetivo: Apresentar um modelo experimental de hérnia de disco e sua validação para estudo da hiperalgesia mecânica e térmica produzidas pelo contato do núcleo pulposo (NP) com as estruturas nervosas envolvidas nessa afecção. Métodos: Foram utilizados ratos Wistar, sendo o NP autólogo retirado da região sacrococcígea e depositado sobre a dura-máter, raiz nervosa ou gânglios das raízes dor-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
1
0
1
Order By: Relevance
“…The Roto-rod, although initially designed for forced ambulation on gait in lesions of the cerebellum 15 , is also used in the grading of joint function in experimental neurological compressions 27 , and joint changes in experimental arthritis of the knees 16,25 . This study showed that the greatest difference occurred in 7 and 14 days after induction.…”
Section: Control Group (Cg)mentioning
confidence: 99%
“…The Roto-rod, although initially designed for forced ambulation on gait in lesions of the cerebellum 15 , is also used in the grading of joint function in experimental neurological compressions 27 , and joint changes in experimental arthritis of the knees 16,25 . This study showed that the greatest difference occurred in 7 and 14 days after induction.…”
Section: Control Group (Cg)mentioning
confidence: 99%
“…Cada disco é feito de uma parte interna gelatinosa e macia cercada por um revestimento externo duro e fi broso. Quando parte desta estrutura sai de sua posição normal, ocorre ruptura do anel fi broso, com subsequente deslocamento da massa central do disco nos espaços intervertebrais, e consequentemente comprimem as raízes nervosas CORDEIRO, 2002;ASSOCIAÇÃO, 2013;NEGRELLI, 2001;GRAVA, 2008).…”
unclassified